The Development of Cooperative Learning Model Team Assisted Individualization with SETS Vision to Increase Science Process Skills - Hanik, Ajik Nur; Sudarmin, Sudarmin; Supardi, Kasmadi Imam (Journal of Innovative Science Education, 2019)
This study aims to increase the science process skills and cognitive learning outcomes of students by applying the development of Team Assisted Individualization (TAI) cooperative learning model with SETS vision. The development of this Team Assisted Individualization (TAI) cooperative learning model with SETS vision is a research and development (R&D). Increasing of science process skills students are explored through observation sheets, then the increasement is analyzed using N-gain. The results showed that Team Assisted Individualization (TAI) cooperative learning model with SETS vision could improve the science process skills of students with the acquisition of N-gain of 0.72 (high) in the experimental class 1 and 0.76 (high) in the experimental class 2. Cognitive learning outcomes of students have increased by 0.54 (moderate) in the experimental classes 1 and 2 with classical completeness of 86.1% and 88.89%. Based on the questionnaire responses, it can be concluded that the implementation of the Team Assisted Individualization (TAI) cooperative learning model with SETS vision effectively increases the science process skills of students.